The diagnostic surprise of solitary anaplastic myeloma of mandible: a rare case report - Vaddepally, Bala Krishna; Sharma, Vikas; Madan, Tanuj; Sengupta, Prashanth; Das, Dibangkar; Zafar, Zia (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Myeloma predominantly affects the elderly who develop a monoclonal protein which is found in their blood and/or urine manifesting as anemia, osteolytic lesions, hypercalcemia, bone pains and renal compromise. Osteolytic lesions are seen in more than 30% of patients with multiple myeloma. However, primary affection of mandible manifest as solitary plasmacytoma of bone occurs in only 4.4% such cases making it a highly unaccustomed entity. The aim of this case report is to present the clinico-pathological profile and the immunohistochemical features of anaplastic myeloma that will be of immense utility in diagnosing its affection of oral cavity and mandible precisely.